Hypoxia‐dependent mRNA expression pattern of splicing factor YT521 and its impact on oncological important target gene expression. Issue 11 (13th June 2013) - Hirschfeld, Marc; Zhang, Bo; Jaeger, Markus; Stamm, Stefan; Erbes, Thalia; Mayer, Sebastian; Tong, Xiaowen; Stickeler, Elmar
Abstract The ubiquitously expressed splicing factor YT521 (YTHDC1) is characterized by alternatively spliced isoforms with regulatory impact on cancer‐associated gene expression. Our recent findings account for the prognostic significance of YT521 in endometrial cancer. In this study, we investigated the hypoxia‐dependency of YT521 expression as well as its differential isoform activities on oncological important target genes. YT521's potential regulatory influence on splicing was investigated by a minigene assay for the specific target gene CD44. Functional splicing analysis was performed by YT521 knock‐down or overexpression, respectively. In addition, YT521 expression was determined under hypoxia. The two protein‐generating YT521 mRNA isoforms 1 and 2 caused a comparable, specific induction of CD44v alternative splicing (P < 0.01). In a number of oncological target genes, YT521 upregulation significantly altered BRCA2 expression pattern, while YT521 knock‐down created a significant regulatory impact on PGR expression, respectively. Hypoxia induced a specific switch towards the processing of two non‐protein‐coding mRNA variants, of which one is described for the first time in this study. The presented study underlines the comparable regulatory potential of both YT521 isoforms 1 and 2, on the investigated target genes in vivo and in vitro. Hypoxia induces a specific switch in YT521 expression pattern towards the two non‐protein coding mRNA variants, the already characterized isoform 3 and the newly discovered exon 8‐skipping isoform. The altered YT521 alternative splicing is functionally coupled with nonsense‐mediated decay and can be interpreted as regulated unproductive splicing and transcription with consecutive impact on the processing of specific cancer‐associated genes, such as BRCA2 and PGR. © 2013 Wiley Periodicals, Inc.